Pathogenetically differentiated management of pregnancy in patients with retrochorial hematoma - Kh. G. Sultangadzhieva; J. Kh. Khizroeva (Акушерство, гинекология и репродукция, 2020)
Introduction. Intrauterine hematomas commonly found in routine ultrasound examinations represent one of causes resulting in early pregnancy loss. The most common is retrochorial hematoma resulting from fetal egg detachment from the uterine wall. Retrochorial hematoma often leads to pregnancy complications and affects gestational process.Aim: to develop a personalized approach to the diagnosis, prevention and management of pregnancy with retrochorial hematomas in the early stages.Materials and methods. A prospective examination of 70 females, aged 22 to 37 years old, with retrochorial hematoma was performed at gestational age ranging from 5 to 12 weeks. Here, we examined serum level for lupus anticoagulant, antiphospholipid antibodies (AFA), antibodies to cardiolipin, fi2-glycoprotein I, to annexin V and prothrombin, and ADAMTS-13. All women were examined for genetic mutations linked to high thrombogenic risk and low thrombogenic risk polymorphisms. Patients were also examined for urinary tract infections.Results. It was found that 43 (61 %) females had aggravated obstetric anamnesis (non-developing pregnancy, spontaneous miscarriage in early stages, antenatal fetal death), whereas 13 (18.5 %) subjects had burdened familial thrombotic history (heart attack, stroke, and thrombosis occurred before the age of 55 years in first-line relatives). In addition, 22 (31.4 %) females were found to have genetic and acquired forms of thrombophilia; 6 (8.5 %) were detected to have circulatory ADAMTS-13 inhibitor; 5 females were confirmed to have decreased blood coagulation factor activity; and 38 (54.2 %) had vaginal dysbiosis.Conclusion. Our work demonstrates that a personified and pathogenetically differentiated algorithm for diagnostics and management of pregnant women with chorionic detachments in early stages allows to lower frequency of early abortions and increases the therapeutic effectiveness.